THE IMPLEMENTATION OF BLOCKCHAIN WITHIN SUPPLY CHAIN TRACEABILITY OF ORGANIC COFFEE BEANS BETWEEN THE FARMERS AND THE COMPANY: A CASE OF VEHGRO B.V - Rachel Ayu Setyaningrum; Rob Berkhof; Fuad Fuad (Diponegoro Journal of Accounting, 2022)
Blockchain is an advanced technology that starts implemented in many factors, such as economy, business, health, etc. In specific, blockchain can also be implemented in the supply chain, which can help the company improve its performance and trust its stakeholders. Furthermore, it will help increase the controlling system for safety and quality of the product, where it becomes customer’s attention because numerous food incidents and accidents in recent years have driven an increase in the need for traceability. The blockchain brings the solution to traceability. This research paper aims to convince VehGro to implement blockchain in its traceability system by providing the opportunities and challenges of blockchain. Then, how this system works in supply chain traceability between the farmers to VehGro. The research method will use an interview with some experts in blockchain and supply chain, and also a literature review to complement the research.